Impact of airport operations and road traffic on the particle number concentration in the vicinity of a suburban airport - Fritz, Sabine; Grusdat , Felix; Sharkey , Rowan; Schneider , Christoph (Frontiers in Environmental Science, 2022)
The impact of airports on ambient air pollution is a major concern due to its impact on public health. This study analyses the sub-micron total particle number concentration (PNC) as a proxy for ultrafine particles in the immediate vicinity of Berlin-Tegel Airport (TXL) based on a mobile measurement campaign in summer 2019. With predominantly westerly winds, 45 measurement runs took place along a 20 km to 30 km route to the east of the airport. The highlights of the study are as follows: • Berlin-Tegel Airport had a distinct but spatially limited impact on the residential areas to the east of the airport. • Particle number concentrations in the lee of the airport are significantly higher than the mean for the entire area. • Locations along the eastward extension of the runways are significantly more affected than those outside the approach corridor. • The impact of airport operations on PNC in the adjacent neighbourhood is comparable to the combined impact of busy roads in the area. The closure of Berlin-Tegel Airport at the end of 2020 should have considerably improved the air quality in the residential areas in the close vicinity of the airport.